Коралина: [повесть] / Нил Гейман - Гейман Нил (АСТ, 2009)
В суперобложке. Экземпляры: ф.22 (20181030) / Инвентарный номер: 58778 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Г 29 / ГРНТИ: 17.82.93 / ББК: 84(7Сое)-44